Mitigating cyber-intrusions in medical devices with agent-based self-healing - Carreon-Rascon, Ana S.; Li, Huayu; Rozenblit, Jerzy W.; Rafajłowicz, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
Medical device security has become a critical focus in the healthcare sector, as increasing connectivity introduces challenges related to patient safety, data confidentiality, and system reliability. To address these concerns, various strategies have been developed, including risk identification, mitigation techniques, and autonomic recovery mechanisms.
Keywords: medical device security; reinforcement learning; self-healing; survival time